THE ROLE OF AIRWAY MUCUS HYPER SECRETION DUE TO KAPHA VITIATION IN TAMAKA SVASA (ASTHMA): PATHOPHYSIOLOGY AND PHARMACOTHERAPEUTIC APPROACH - Yusuf, *Ansary Panamthanathil; A, Shajahan M (International Journal of Ayurveda and Pharma Research, 2017)
Tamakasvasa (asthma) is a mucous hypersecretory respiratory disease. The inspissated mucus produced by vitiated Kapha obstructs the bronchi and other small air passages in the pathological development of the disease. Physiologically Kapha dosa provides strength (Bala) to the body due to the intrinsic qualities unctuousness (Snigda), coldness (Sita), heaviness (Guru), slowness (Manda), smoothness (Slasna), softness (Mrisna), stability (Sthira) etc. Being an organ in the specific site of Kapha dosha i.e., thorax (Uras), production of mucus in lungs is normal. Etiological factors that irritate respiratory tract stimulate inflammatory process and due to this, mucus is produced in excess. Due to the excessive vitiation of qualities of Kapha the mucus turns highly viscous and the normal clearance of mucus by airflow and ciliary function is hampered. Thus gelatinous mucus plugs tend to develop in the airways. The gel-forming MUC genes MUC2, MUC5AC and MUC5B commonly seen in respiratory secretions and stomach, duodenum, gall bladder etc have major role in the formation of airway mucus. Due to the ingestion of unwholesome food stomach (Amasaya) where Kapha reside, act as the organ of origin of the disease. The main pharmacotherapeutic objective in the management of Tamakasvasa is reduction of airway obstruction and airflow limitation by enhancing mucus clearance. This can be achieved by altering the rheological properties of bronchial mucus and inhibition of mucus hyper secretion and airway hyper responsiveness by procedure based therapies and pharmacological methods of Sleshmavilayana, Srotomardavakarana and rationale use of taste specific drug therapy (Rasapravicarana chikitsa).